ICT literacy – the requirement of foreign countries modern education systems (experience of the USA) - Malitskaya, І.Д. (Journal of Information Technologies in Education (ITE), 2009)
In the article the development and present days situation of information and communication technologies and Technological standards implementation in an education system of the USA is analysed.